Improving the Quality of Colloidal System Learning through Lesson Study with Inquiry-Based Experimental Methods - Wandansari, Umi; Nirvana, Indhie; Sharma, Neelam (Journal of Chemical Learning Innovation, 2024)
Purpose of the study: The purpose of this study is to determine the lesson study learning process using the guided inquiry-based experimental method on the main material of colloidal systems at Madrasah Aliyah Darut Taqwa. Methodology: This study employed a descriptive qualitative method with a lesson study approach (plan–do–see cycle). Instruments included observation sheets (Likert scale 1–5), interview guides, and documentation checklists. Data were collected through observation, semi-structured interviews, and document review. Data analysis used the Miles and Huberman model. Data processing utilized Microsoft Excel. Main Findings: The results of this study indicate that lesson study activities involve three stages: planning (Plan), implementation (Do), and reflection (See). Prior to this activity, initial observations were conducted to compare the pre-lesson and post-lesson study sessions. As a result, teachers' ability to manage learning improved. For example, the ability to guide problem formulation increased from 41.25% to 53.75%. Improvements also occurred in the ability to conduct experiments, analyze and present results, and communicate. Based on these data, lesson study activities can improve the quality of learning. Novelty/Originality of this study: This study introduces an integrated implementation of lesson study with guided inquiry-based experimental methods specifically applied to colloidal system learning. It advances existing knowledge by emphasizing collaborative teacher development alongside student-centered inquiry processes. The study provides new insights into how iterative lesson study cycles enhance instructional quality, teacher competence, and active student engagement in chemistry learning contexts.